The association between patellofemoral grind and synovitis in knee osteoarthritis: data from the osteoarthritis initiative - Deng, Hui; Wu, Yongzhong; Fan, Zaiwei; Tang, Wubing; Tao, Jun (Frontiers in Medicine, 2023)
Objective Patellofemoral grind refers to the tender behind the knee cap while contracting the quadriceps muscle during the patellar grind test. The present investigation aims to elucidate the association between patellofemoral grind and synovitis in the knee osteoarthritis (KOA). Method A total of 1,119 knees with complete patellofemoral grind and synovitis assessment records from the Osteoarthritis Initiative (OAI) were investigated in this study. The Magnetic Resonance Imaging at baseline, 12 months, and 24 months of follow-up were employed to evaluate synovitis. Frequent patellofemoral grind was operationally defined as occurring more than twice at three different time points. In addition, a sensitivity stratification was conducted to examine gender differences. Results The study participants had an average age of 61 years, with 62.4% being female. The findings revealed that baseline patellofemoral grind was significantly associated with changes in synovitis at follow-up (odds ratio [OR]: 1.44, confidence interval [CI]: 1.04–1.98) and was also linked to synovitis worsening over 24 months (OR: 1.67, CI: 1.13–2.46) in all subjects. For the subjects with frequent patellofemoral grind, this correlation was more significant (OR: 1.50, CI: 1.03–2.16; OR: 1.71, CI: 1.09–2.67). In the context of sensitivity stratification, it was observed that the baseline and frequent patellofemoral grind in females exhibited a significant correlation with synovitis. However, no significant correlation was found in males. Conclusion Patellofemoral grind may serve as a potential risk factor of synovitis in knee osteoarthritis, particularly among female patients, and thus, necessitates close monitoring and management by clinical physicians.